2015
DOI: 10.9738/intsurg-d-14-00042.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Surgical Site Infection in Older Patients in a Cohort Survey: Targets for Quality Improvement in Antibiotic Prophylaxis

Abstract: The aims of the present study were to: (1) assess surgical site infection (SSI) incidence in a cohort of surgical patients and (2) estimate the compliance with national guidelines for perioperative antibiotic prophylaxis (PAP). SSIs, among the most common health care-associated infections, are an important target for surveillance and an official priority in several European countries. SSI commonly complicates surgical procedures in older people and is associated with substantial attributable mortality and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
(25 reference statements)
0
15
0
1
Order By: Relevance
“…By contrast, our analysis demonstrated that prevalence of HAIs remained stable from 2016 to 2018, with a negative but not significant peak in 2017. This was partly comforting since patients participating in the Sicilian PPSs became older and more severe over the years, although it is well known that aging and disease severity are risk factors for HAIs [ 26 , 27 , 28 ]. In line, we noted an increasing trend in the presence of invasive devices from 2016 to 2018, but it also did not result in an increased prevalence of HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, our analysis demonstrated that prevalence of HAIs remained stable from 2016 to 2018, with a negative but not significant peak in 2017. This was partly comforting since patients participating in the Sicilian PPSs became older and more severe over the years, although it is well known that aging and disease severity are risk factors for HAIs [ 26 , 27 , 28 ]. In line, we noted an increasing trend in the presence of invasive devices from 2016 to 2018, but it also did not result in an increased prevalence of HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO guidelines [8] aim to achieve this, but several studies have shown that adherence is not optimal [33][34][35]. In comparison to a Brazilian study [15], this study found a higher rate of administering surgical antibiotic prophylaxis (96.0% vs 77.6%), which was comparable to an Italian study [16] (96.0% vs 96.8%). The effectivity of surgical antibiotic prophylaxis may depend on the type of surgery performed [36], and as a result, if a surgeon is aware of this, the adherence to SSI prevention guidelines might be expected to be improved.…”
Section: Surgical Antibiotic Prophylaxismentioning
confidence: 45%
“…However, even if age group does not have a direct association, it can interplay with other factors related to the procedure. Older patients tend to have more frequent emergency surgeries than younger ones and longer operating times [16]. This study shows that both of these factors increase the likelihood of poor adherence to SSI prevention guidelines, with surgeons demonstrating poorer adherence in emergency surgeries and with longer operating times.…”
Section: Patient Age and Application Of Ssi Preventive Measuresmentioning
confidence: 74%
See 1 more Smart Citation
“…Esta población se caracteriza por tener un patrón de comorbilidades, las cuales desde el punto de vista quirúrgico son determinantes para el surgimiento de algunas complicaciones durante su estancia hospitalaria completa. Identificar estas comorbilidades y condiciones asociadas permitirán disminuir tanto las complicaciones intrahoperatorias como las postoperatorias para lograr no solo un buen acto quirúrgico, sino uno exitoso 5,6 .…”
Section: Introductionunclassified